Different Biological Action of Oleic Acid in ALDH(high) and ALDH(low) Subpopulations Separated from Ductal Carcinoma In Situ of Breast Cancer - Kim, Hoe Suk (PLoS One, 2016)
The mechanisms underlying breast cancer progression of ductal carcinoma in situ (DCIS) associated with fatty acids are largely unknown. In the present study, we compared the action of oleic acid (OA) on two human DCIS cell lines, MCF10DCIS.COM (ER/PR/HER2-negative) and SUM225 (HER2 overexpressed). OA led to a significant increase in proliferation, migration, lipid accumulation and the expression of lipogenic proteins, such as SREBP-1, FAS and ACC-1, in MCF10DCIS.COM cells but not SUM225 cells. The ALDH(high) subpopulation analyzed by the ALDEFLUOR assay was approximately 39.2±5.3% of MCF10DCIS.COM cells but was small (3.11±0.9%) in SUM225 cells. We further investigated the different biological action of OA in the distinct ALDH(low) and ALDH(high) subpopulations of MCF10DCIS.COM cells. OA led to an increase in the expression of ALDH1A1, ALDH1A2 and ALDH1A3 in MCF10DCIS.COM cells. SREBP-1 and ACC-1 were highly expressed in ALDH(high) cells relative to ALDH(low) cells, whereas FAS was higher in ALDH(low) cells. In the presence of OA, ALDH(high) cells were more likely to proliferate and migrate and displayed significantly high levels of SREBP-1 and FAS and strong phosphorylation of FAK and AKT relative to ALDH(low) cells. This study suggests that OA could be a critical risk factor to promote the proliferation and migration of ALDH(high) cells in DCIS, leading to breast cancer progression.